Planck 2013 Cosmology Results: a Review - José Alberto Rubino-Martín (Acta Polytechnica CTU Proceedings)
This talk presents an overview of the cosmological results derived from the first 15.5 months of observations of the ESA’s Planck mission. These cosmological results are mainly based on the Planck measurements of the cosmic microwave background (CMB) temperature and lensing-potential power spectra, although we also briefly discuss other aspects of the Planck data, as the statistical characterization of the reconstructed CMB maps, or the constraints on cosmological parameters using the number counts of galaxy clusters detected by means of the Sunyaev-Zeldovich effect in the Planck maps. All these results are described in detail in a series of papers released by ESA and the Planck collaboration in March 2013.